Metal-dielectric black matrix for display devices - Chang Won Park; Joon-Bae Lee; Young Rag Do; Shepeliavyi, P.; Michailovska, K.; Indutnyy, I.; Kudryavtsev, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Technology of metal-dielectric coating deposition for manufacturing a light-absorbing black matrix on a panel of color cathode-ray tubes is described. The coating is prepared using thermo-vacuum evaporation of SiO-Cr mixture. That yields in a thin-layer non-uniform (by its composition) structure SiOx-Cr. It is shown that the coating prepared in this way is achromatic and has low reflectivity (~1%) from the side of a transparent panel. The index of diffuse light scattering measured for such metal-dielectric coating does not exceed 0.1% in the spectral range of 400-700 nm. It is shown that black matrix based on the coating SiOx-Cr can be produced using the methods of direct or lift-off photolithography, with organic or non-organic photoresist. Color CRT with these metal-dielectric black matrixes on their panels have increased image contrast as compared with the colloid-graphite ones.